THE ANALYSIS OF THE ROLE OF DAKWAH IN FORMING THE CHARACTER OF THE UPI CIBIRU CAMPUS DAKWAH INSTITUTION - Muhamad Fadhly Rafiansyah; Annisa Isnaini Tsaniya; Firli Rucita Sundari; Muhammad Syaiq Dhiyaulhaq (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2024)
This article investigates the role of da'wah in shaping student character at the UPI Cibiru Campus Dakwah Institute. A qualitative research approach was used by conducting in-depth interviews and observations with members of the institution and related stakeholders. The results showed that da'wah has a significant impact in shaping student character, including increased spiritual awareness, moral values, and leadership development. The implication of this finding is the importance of the role of da'wah institutions in improving the quality of character education in the campus environment, as well as the expansion of understanding and application of religious values in student life. In conclusion, this article underscores the urgency of integrating da'wah as an integral part of holistic education to strengthen student character and support the formation of more meaningful individuals in society.